Association between anthropometric measurements and dental caries among children in Asia: A systematic review and meta-analysis / Rokiah Mamikutty - Rokiah, Mamikutty (2021)
Overweight and dental caries among children is increasing in Asia. The association between anthropometric measurements and dental caries is inconclusive and not representing the Asian context. Aim: To assess the association between anthropometric measurements and caries among children in Asia by regions, sugar consumption per-capita, and SES of the countries. Methods: The review was registered with PROSPERO and conducted following PRISMA guidelines. Twenty-six databases were employed for searching the eligible studies from inception until Jun 2019. Two reviewers independently screen, select studies, perform data extraction, and risk bias assessment, with discrepancies resolved by discussion and reference to the third reviewers. Meta-analysis was performed using a random-effect model. Heterogeneity was assessed using chisquare and quantify with Higgin I2 statistic. A sensitivity analysis and reporting bias was assessed using funnel plots. Subgroup analysis was conducted by regions, sugar consumption per-capita, and socio-economic of the countries. Harvest plot was employed when meta-analysis is inappropriate. Quality of evidence was rated with GRADE. Results: 4532 studies retrieved. Sixty-six studies were included after deduplication, title, and abstract and full-text screening. Fifty-three studies were pooled in meta-analysis and 13 studies analysed by Harvest plot. For primary dentition, BMI was negatively associated with caries prevalence and caries severity. Overweight (OR: 0.64; 95%CI 0.53, 0,77) or obese children (OR: 0.58; 95%CI 0.44, 0.77) were less likely to have caries compared to normal weight, and underweight children (SMD: 0.15; 95%CI 0.05, 0.25) have caries severity compared to normal weight. No significant association iv was observed between BMI, WC, WHtR, SFT and caries in permanent dentition. In mixed dentition, obese children (OR: 0.60; 95%CI 0.52, 0.69) are less likely to have caries than normal weight. In South Asia, West Asia, East Asia, high-income, upper- and lowermiddle-income countries, overweight children are less likely to have caries in primary dentition than normal-weight children. Highest inequalities are in South Asia, countries with sugar consumption per-capita higher than the WHO recommendation and lowermiddle-income countries. In West Asia, East Asia, high-income, and upper-middleincome countries, obese children are less likely to have caries in primary dentition than normal-weight children. Highest inequalities are in West Asia and high-income countries. Underweight children have more caries in primary dentition in South Asia, East Asia, and West Asia, the highest inequalities in South Asia. In permanent dentition, underweight children from South Asia are less likely to have caries. Also, in lower-middle-income countries, underweight children less likely to have more caries in permanent dentition than normal-weight children (positive association). In high-income countries, underweight children have more severe caries than normal-weight children. Overweight and obese children are less likely to have caries in permanent dentition than normalweight children in West Asia, a negative association. These findings are rated as low to very low by GRADE. Conclusion: In Asia, the negative association between BMI and caries is revealed in the primary dentition. Regions, sugar consumption per-capita, and SES of countries influenced the association between BMI and caries. Future studies for other anthropometric measurements than BMI, studies from South East Asia and Central Asia are required.